THE MAGIC TOY BOOK (Educational Technologies Ltd. Place of publication not identified, 2004)
"The Land of Toys: A Book About Looking After Our Toys" is a playful and imaginative story about a group of children who are transported to a magical land where their toys come to life. In this world, the toys explain the importance of being cared for, showing the children how neglect or rough play can damage them. As the children learn how to clean, repair, and treat their toys with kindness, they understand the value of responsibility and respect for their belongings. The book delivers a meaningful message about taking care of the things we love and fostering a sense of responsibility from a young age.